Oliver Cromwell and The ‘Cromwellian’ Settlement Of Ireland - Cunningham, John (The historical journal, 2010)
Oliver Cromwell remains a deeply controversial figure in Ireland. In the past decade, his role in the conquest has received sustained attention. However, in recent scholarship on the settlement of Ireland in the 1650s, he has enjoyed a peculiarly low profile. This trend has served to compound the interpretative problems relating to Cromwell and Ireland which stem in part from the traditional denominational divide in Irish historiography. This article offers a reappraisal of Cromwell's role in designing and implementing the far-reaching ‘Cromwellian’ land settlement. It examines the evidence relating to his dealings with Irish people, both Protestant and Catholic, and his attitude towards the enormous difficulties which they faced post-conquest. While the massacre at Drogheda in 1649 remains a blot on his reputation, in the 1650s Cromwell in fact emerged as an important and effective ally for Irish landowners seeking to defeat the punitive confiscation and transplantation policies approved by the Westminster parliament and favoured by the Dublin government.